Skin Color Cues to Human Health: Carotenoids, Aerobic Fitness, and Body Fat - Perrett, David I.; Talamas, Sean N.; Cairns, Patrick; Henderson, Audrey J. (Frontiers in Psychology, 2020)
Colourful carotenoid ornaments are sexually selected signals of health in many species. In humans too, carotenoids could provide a perceptible cue to health as they impart an attractive yellow-orange colour to skin. Increasing carotenoid pigmentation and skin yellowness is associated with increased fruit and vegetable intake, but whether other aspects of human health benefit skin colour is unknown. Carotenoids, as antioxidants, help maintain oxidative balance but are expended in this role. Therefore any health factor affecting oxidative balance could alter the quantity of carotenoids available to colour skin. Exercise increases endogenous antioxidant capacity and consequently may decrease expenditure of carotenoids. Fitness could also raise skin carotenoids by lowering body fat (a source of oxidative stress). Here we investigate the relationship between skin colour (measured spectrophotometrically), aerobic fitness (measured by estimating the maximum volume of oxygen that a person can use per unit of time, VO2 max) and body fat. In a cross-sectional design we find that both higher aerobic fitness and lower body fat are predictors of skin yellowness, independent of each other and dietary fruit and vegetable intake. In a longitudinal design over 8 weeks, we found that increase in fitness and decrease in body fat, were independently associated with an increase in skin yellowness. Change in self-reported stress and sleep were further predictors of skin yellowness indicating a more general relation between health and skin tone. Simulations of the skin colour associated with higher fitness were found more to appear healthier. Hence, our results suggest that increasing cardiovascular fitness and decreasing fat levels produce a healthier skin colour. Such findings have repercussions for public health because improved attractiveness can provide an incentive for a healthier lifestyle, including exercise and weight regulation.